Organ distribution of erythropoietin messenger RNA in normal and uremic rats. - Tan, C; Eckardt, K; Ratcliffe, P (1991)
We used RNAase protection assays to measure low levels of erythropoietin messenger RNA (EPO mRNA) in the organs of unstimulated rats, and to compare basal and stimulated levels of EPO mRNA in the kidneys and extrarenal organs of rats rendered uremic by subtotal nephrectomy, with pair-fed controls. Using this sensitive assay, EPO mRNA was measured in the kidneys of unstimulated control animals and was detectable, at lower levels, in the liver and lung. After exposure to hypoxia, there was a 150-fold increase in renal EPO mRNA. Hepatic EPO mRNA was also greatly increased and accounted for 39 +/- 10% of the total. The small quantity of EPO mRNA in lung did not increase, but EPO mRNA became detectable in spleen. Animals subjected to subtotal nephrectomy became uremic and anemic (hematocrit 0.32 +/- 0.04 vs. 0.43 +/- 0.04 in controls, P = 0.002), but serum EPO concentrations were not significantly increased (32 +/- 9 vs. 24 +/- 6 mU/ml, P = 0.14). However, after hypoxic exposure, uremic animals increased serum EPO concentrations greatly, although the response was less than in controls (349 +/- 82 vs. 1009 +/- 238 mU/ml, P = 0.002). After hypoxia, extrarenal EPO mRNA levels in uremic animals were similar to controls. In particular, the large hepatic potential for EPO mRNA synthesis was unchanged but accounted for a greater proportion (84 +/- 5%) of the total EPO mRNA. The renal EPO mRNA content was reduced, as expected, after subtotal nephrectomy, but increased 50-fold after hypoxia. In this model of chronic renal failure, despite anemia, a large potential for EPO synthesis exists in liver and remnant kidney.